Trichoderma sp. AH pretreatment improves organic oxygen composites from supercritical alcoholysis of wheat straw - Quanxi Zheng; Chuanyong Yan; Lei Zhang (PLoS ONE, 2025)
Electrospray ionization fourier transform ion cyclotron resonance mass spectrometry was applied to evaluate the organic oxygen composites (OOCs) in methanol fraction derived from the supercritical alcoholysis of original and pretreated straw (WS) utilizing Trichoderma sp. AH. In the methanol-soluble fraction (MSF) of untreated and preconditioned WSs, On (n =  1–10), with double bond similar values of 1–28 and carbon atom numbers of 4–35, was the most predominant OOCs in the negative ion mode. O5 and O4 were the most prominent OOCs in the MSF of original and preconditioned WS, respectively. These results assist in comprehending the impact of Trichoderma sp. AH pretreatment on the specificity, and transformation of OOCs in WS alcoholysis and the application of MSF to manufacture fuel source.